Design of an AI-Driven Smart Engineering Event Portal with Multi-Agent Recommendation and Analytics Framework - Prof. Jyotsna Nanajkar,; Sanika Kulkarni,; Shravani Nandedkar,; Sujata Nikam,; Sejal Khopade, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Academic event management continues to struggle with fragmentation, poor accessibility, and lack of personalization in today's digital education ecosystem. In order to improve event discovery and participation, this article outlines the architecture of an AI-driven Smart Engineering Event Portal that combines analytics, hybrid recommendation models, and multi-agent frameworks. The suggested system integrates content-based and collaborative filtering for personalized recommendations and Agentic AI for autonomous interaction, drawing on ideas from previous works such as AI-Based Event Management Web Application (Hada et al., 2022), Agentic AI Multi-Agent Recommender Framework (Portugal et al., 2024), and GoWIS Hybrid Event Recommendation System (Bhor et al., 2024). The solution, which was developed using the MERN stack, allows students to explore events according to their preferences while universities can use real-time dashboards to analyze participation.
Keywords: Event Management System; Recommender System; Agentic AI; MERN Stack; Data Analytics; Multi-Agent Framework